TMT-based quantitative proteomics analysis reveals the effect of bovine derived MFG-E8 against oxidative stress on rat L6 cells. Issue 16 (25th June 2021) - Guan, Kaifang; Li, He; Chen, Haoran; Qi, Xiaofen; Wang, Rongchun; Ma, Ying
Abstract : The procedure of TMT-based quantitative proteomics analysis and the subsequent verification of MFG-E8 on oxidative stress response. Abstract : Sarcopenia is an aging-associated oxidative stress-induced mitochondrial dysfunction characterized by a decline in skeletal muscle mass, strength and function. Milk fat globule-EGF factor 8 (MFG-E8) is a secreted matrix glycoprotein that plays a crucial role in regulating tissue homeostasis and protecting against skeletal muscle injury. To explore the molecular mechanism of MFG-E8 in ameliorating the rotenone (Rot)-induced L6 skeletal muscle cell oxidative stress injury, differential proteomics of inner L6 cells was conducted. Tandem mass tag (TMT) labeling combined with mass spectrometry (MS) was performed to find associations among control, Rot and Rot + MFG-E8 groups. Over 3248 proteins were identified in the L6 cells. A total of 639 significantly differential proteins were identified, including 294 up-regulated proteins (>1.2 fold) and 345 down-regulated proteins (<0.83 fold) after the exogenous intervention of MFG-E8. Based on the analysis of Gene Ontology (GO), STRING and KEGG databases, MFG-E8 relieves oxidative stress induced-L6 cell damage by regulating the expression of these differential proteins mainly via carbon metabolism, glutathione metabolism and mitochondria-mediated metabolic pathways, e.g. carbohydrate, lipid and amino acid metabolism. Furthermore, to verify the protective effect of MFG-E8 on oxidative stress injured L6 cells, the levels of intracellular reactive oxygen species (ROS), nicotinamide adenine dinucleotide/reduced nicotinamide adenine dinucleotide (NAD + /NADH) contents and the protein expression of peroxisome proliferator-activated receptor-γ coactivator-1α (PGC-1α) were detected.